In Vitro Cytotoxic Evaluation of MgO Nanoparticles and Their Effect on the Expression of ROS Genes - Kumaran, Rangarajulu Senthil; Choi, Yong-Keun; Singh, Vijay; Song, Hak-Jin; Song, Kyung-Guen; Kim, Kwang Jin; Kim, Hyung Joo (MDPI, 2015)
Water-dispersible MgO nanoparticles were tested to investigate their cytotoxic effects on oxidative stress gene expression. In this in vitro study, genes related to reactive oxygen species (ROS), glutathione S-transferase (GST) and catalase, were quantified using real-time polymerase chain reactions (molecular level) and molecular beacon technologies (cellular level). The monodispersed MgO nanoparticles, 20 nm in size, were used to treat human cancer cell lines (liver cancer epithelial cells) at different concentrations (25, 75 and 150 mu g/mL) and incubation times (24, 48 and 72 h). Both the genetic and cellular cytotoxic screening methods produced consistent results, showing that GST and catalase ROS gene expression was maximized at 150 mu g/mL nanoparticle treatment with 48 h incubation. However, the genotoxic effect of MgO nanoparticles was not significant compared with control experiments, which indicates its significant potential applications in nanomedicine as a diagnostic and therapeutic tool.
Keywords: OXIDATIVE STRESS; OXIDE NANOPARTICLES; TOXICITY; CELLS; MECHANISMS; PROTECTION; PARTICLES; NRF2; VIVO